2019
DOI: 10.1111/aogs.13626
|View full text |Cite
|
Sign up to set email alerts
|

Shock index thresholds to predict adverse outcomes in maternal hemorrhage and sepsis: A prospective cohort study

Abstract: IntroductionShock index (SI) is a predictor of hemodynamic compromise in obstetric patients. The SI threshold for action is not well understood. We aimed to evaluate SI thresholds as predictors of outcomes in obstetric patients.Material and methodsWe undertook a prospective cohort study at three South African hospitals of women with postpartum hemorrhage (n = 283) or maternal sepsis (n = 126). The “first” and “worst” SI following diagnosis were recorded. SI was compared with conventional vital signs as predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
1
23
2
1
Order By: Relevance
“…In a prospective study involving women with postpartum haemorrhage or sepsis, the SI was found to be a consistent predictor of adverse outcomes compared with conventional vital signs. 36 The introduction of maternal and neonatal sepsis scoring systems may be the first step towards achieving a reliable surveillance system for sepsis in SSA. Electronic surveillance tools which monitor physiological parameters should be developed to facilitate automatic recognition of the early signs of sepsis in health facilities.…”
Section: Improve the Early Identification Of Sepsis In Facilitiesmentioning
confidence: 99%
“…In a prospective study involving women with postpartum haemorrhage or sepsis, the SI was found to be a consistent predictor of adverse outcomes compared with conventional vital signs. 36 The introduction of maternal and neonatal sepsis scoring systems may be the first step towards achieving a reliable surveillance system for sepsis in SSA. Electronic surveillance tools which monitor physiological parameters should be developed to facilitate automatic recognition of the early signs of sepsis in health facilities.…”
Section: Improve the Early Identification Of Sepsis In Facilitiesmentioning
confidence: 99%
“…The collected data included HR in the emergency department (ED), SBP in the ED, age, sex, trauma, pregnancy status, acute myocardial infarction, sepsis, chronic respiratory disease (previous history of chronic obstructive pulmonary disease, chronic bronchitis, asthma, bronchiectasis, interstitial pneumonia, pulmonary tuberculosis, or lung cancer), and intracranial disease (having suffered from stroke, transient ischemic attack, encephalitis, encephalopathy, seizure, brain tumour, hydrocephalus, concussion, cerebral contusion, or traumatic subarachnoid haemorrhage at arrival to ED). These speci c patient characteristics were included since many previous studies have examined the ability of the SI to predict mortality or other critical conditions in those with trauma, pregnancy, acute myocardial infarction, sepsis, and intracranial disease [2][3][4][5][6][7][8][9][10][11][12][13][14][15], and because HR and SBP of aged or chronic respiratory disease patients are known to exhibit speci c dynamics [24][25][26].…”
Section: Study Protocolmentioning
confidence: 99%
“…The shock index (SI) is an indicator of the severity of hypovolemic shock and is calculated by dividing the heart rate (HR) by systolic blood pressure (SBP) [1]. It serves to predict the mortality, need for blood transfusion, or necessity of intensive care unit admission among patients with trauma [2][3][4][5][6][7], postpartum haemorrhage [8,9], acute myocardial infarction [10,11], stroke [12,13], sepsis [14,15], and other critical conditions [16,17]. Numerous previous studies have demonstrated that the SI demonstrates superior prediction for mortality to traditional vital signs, although it has some limitations, including its low sensitivity especially for the elderly or obstetric patients [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Given that both parameters, pulse and systolic blood pressure, are altered in pregnancy, such a ratio may be a useful measure to compare haemodynamic change in the pregnant and non-pregnant patients. Further studies are required to determine its clinical value [42]. There is a growing interest in establishing the variations to the sepsis response in pregnancy and the puerperium at an immunological and cardiovascular level as this may contribute to delayed detection as well as the speed of progression and severity of disease in these patients.…”
Section: Maternal Sepsismentioning
confidence: 99%